Загальнотеоретична характеристика підстав звільнення від юридичної відповідальності - Калєніченко, Л. І.; Kalenichenko, L. I.; Калєніченко Лідія Іванівна (Право і безпека. – 2017. – № 3 (66). – С. 26–32, 2017)
Виокремлено та проаналізовано основні суттєві риси підстав, що звільняють від юридичної відповідальності, сформульовано поняття «підстави звільнення від юридичної відповідальності». Їх автор визначає як визначені законодавством обставини, за наявності яких особа, що порушила суб’єктивні права або вчинила правопорушення, не притягається до юридичної відповідальності. До основних ознак підстав звільнення від юридичної відповідальності віднесено: 1) зв’язок з юридично значущою неправомірною поведінкою; 2) формальне закріплення на законодавчому рівні; 3) реалізацію спеціальним суб’єктом; 4) специфічні юридичні наслідки (за умови реалізації підстав звільнення від юридичної відповідальності держава відмовляється від застосування відповідних заходів державно-правового примусу).

The basic essential features of the grounds, which relieve from legal liability have been singled out and analyzed; the notion of “the grounds for the relief of legal liability” has been formulated. The author determines them as circumstances defined by the law, in the presence of which a person, who violates subjective rights or committed an offense, is not brought to legal liability. The main grounds for relief of legal liability include: 1) relation to legally significant unlawful conduct; 2) formal consolidation at the legislative level; 3) the implementation by a special subject; 4) specific legal consequences (in case of the implementation of the grounds for the relief of legal liability, the state refuses to apply appropriate measures of state and legal coercion). The main types of grounds, which relieve from legal liability, have been distinguished according to the following criteria: 1) depending on the object of legal regulation; 2) depending on the mandatory application; 3) depending on the volitional character.

Выделены и проанализированы основные существенные черты оснований, которые освобождают от юридической ответственности, сформулировано понятие «основания освобождения от юридической ответственности». Их автор определяет как определённые законодательством обстоятельства, при наличии которых лицо, нарушившее субъективные права или совершившее правонарушение, не привлекается к юридической ответственности. К числу основных признаков оснований освобождения от юридической ответственности отнесены: 1) связь с юридически значимым поведением; 2) формальное закрепление на законодательном уровне; 3) реализация специальным субъектом; 4) специфические юридические последствия (при условии реализации оснований освобождения от юридической ответственности государство отказывается от применения определённых мер государственно-правового принуждения).
General theoretical characteristics of the grounds for the relief of legal liability
Общетеоретическая характеристика оснований освобождения от юридической ответственности
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; юридична відповідальність; звільнення від юридичної відповідальності; підстави звільнення від юридичної відповідальності; невідворотність відповідальності; legal liability; relief of legal liability; inevitability of liability; юридическая ответственность; освобождение от юридической ответственности; неотвратимость ответственности